Randomized clinical trial to compare efficacy and safety of repeated courses of rituximab to single-course rituximab followed by maintenance mycophenolate-mofetil in children with steroid dependent nephrotic syndrome - Basu, Biswanath; Erdmann, Stella; Sander, Anja; Mahapatra, T. K. S.; Schaefer, Franz (BMC nephrology, 2020)
Approximately 30% of children with idiopathic nephrotic syndrome develop a complicated course with frequent relapses or steroid dependency. Rituximab, a B cell depleting monoclonal antibody, is a safe and effective alternative to steroids or other immunosuppressants for achieving and maintaining remission in this population at short term. Despite the good initial response relapses inevitably occur after regeneration of B lymphocytes, necessitating either repeat courses of rituximab or addition of another steroid-sparing immunosuppressant.